Auricular therapy for chronic pain management in adults: A synthesis of evidence. Issue 2 (May 2015) - Zhao, Hong-Jia; Tan, Jing-Yu; Wang, Tao; Jin, Lang
Abstract: Objective: To evaluate the efficacy and safety of auricular therapy (AT) on chronic pain. Methods: A systematic review. Randomized controlled trials investigating AT for chronic pain were retrieved and RevMan 5.3 was used for meta-analysis. Results: Fifteen trials were included. The overall assessment indicated that AT could be a promising intervention for chronic pain relief. Meta-analyses showed that AT decreased pain intensity, especially for chronic low back pain and chronic tension headache. The lasting effect of AT was not obvious, and it began to diminish 3 months after the completion of treatment. Conclusions: AT may positively control pain intensity for patients with chronic pain. However, due to the significant heterogeneity and methodological flaws identified in the analyzed trials, the current evidence on AT for chronic pain management is still uncertain. More rigorously designed large-scale randomized controlled trials are required to evaluate the efficacy of AT for patients with chronic pain. Highlights: Chronic pain is a major health problem worldwide. Auricular therapy (AT) can be a promising intervention for chronic pain relief. Rigorously designed trials are warranted to strengthen the evidence of AT for chronic pain control.